Institutional Factors and Gender Role in Rural Technology Adoption in Nigeria - Sofoluwe, N. A. (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Rural development agenda could be affected by institutional issues and gender differences in access to rural based technology. This study examines the influence of institutional factors from gender perspective, on rural technology adoption decision of rural households in Nigeria. Primary data were collected for the study using structured questionnaire. The data collected from randomly sampled respondents were fitted to Heckman selection model. Results show that access to credit and new seed technology exerts significant influence on adoption decisions of male and female rural households. While institutional factor of access to credit affects both male and female, access to the technology is more favourable to male. The findings suggest the need for inclusive support, through institutional intervention, for both rural male and female households to achieve rural developmental objectives. Keywords: rural development, gender, credit access, adoption, heckman.